Proposal for a public management model to improve job performance in directors of UGEL Bagua schools - Rosas Carranza Guevara; Manuel Eduardo Vilca Tantapoma; Benjamin David Carril Verastegui; Manuel Tiberio Valentin Puma (Universidad Ciencia y Tecnología, 2022)
This research proposes a public management model that improves the work performance of the executives of the initial education organizations of the UGEL Bagua. Being explanatory in nature with a quantitative approach, with a non-experimental cross-sectional design. The questionnaire with a Likert scale was used on a sample of 40 managers. Pointing out that according to the dimension of management of conditions for the improvement of learning (47.5%) and the dimension of the orientation of the pedagogical processes for the improvement of learning (57.5%) they were found at a good level. A conclusion is that it is important to apply the public administrative model to optimize work performance, with uniform, democratic criteria that are agreed upon for the performance of management and academic activities in all educational organizations at the initial level, thus allowing the improvement of work performance.Keywords: Public management, educational institutions, work performance, pedagogical processes.